Projected range overlap between the predator Teretrius nigrescens and the invasive stored product pest Prostephanus truncatus expands under climate change - Rachel R. Harman; William R. Morrison, III; Alison R. Gerken (Biological Control)
The larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), is a forest-dwelling destructive pest of stored corn and cassava native to Central America and invasive in Africa. Its native predator, Teretrius nigrescens Lewis (Coleoptera: Histeridae), was released in Africa as a biocontrol agent with some success. In the native range, the predator does control the pest, which has likely limited the pest’s movement northward into the United States. However, responses to future changes in climate may impact the ranges of insect species differently and, consequently, may alter the efficacy of biological control. Thus, we (1) used bioclimatic variables and known occurrences to model the potential distribution of T. nigrescens and P. truncatus in its native and introduced ranges, (2) projected future potential distribution out to the years 2050 and 2070 under low and high climate change scenarios (representative concentration pathways (RCP) 2.6 and 8.5, respectively), and (3) compared the ranges and important bioclimatic variables between the species. We used the platform Wallace, which employs an optimized maximum entropy (MaxEnt) model. Highly suitable areas (>75 %) of T. nigrescens current distribution totaled 5.5 % and 8.2 % for the Americas and Africa, respectively. Areas of high suitability are estimated to double (RCP2.6) and to triple (RCP8.5) by 2050 and then increase again 1.3 times by 2070 under RCP8.5. Projected T. nigrescens distributions are much smaller in area and percentage expansion than prey. The overlap of current highly suitable distributions is lower in the native (4.5 %) than the African range (22.2 %); however, the overlap is expected to increase by 86 % in the Americas and 63 % in Africa under the 2070 RCP8.5. Bioclimatic variables important to the models show that low temperatures and variability in temperature and humidity limit the biocontrol agent’s distribution to a greater degree than the prey.